Pengaruh Beban Kerja Terhadap Efektivitas Kerja Karyawan Di Dinas Perdagangan Kota Bandung - Febrian Valentino; Widwi Handari Adji (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this paper is to analyze the effect of workload on the effectiveness of work work of employees of the Ministry of Trade. This research method is quantitative, with the number of samples taken as many as 31 in the city of Bandung. Data collection techniques use primary data generated from questionnaires that have been tested for validity, reliability, partial hypothesis (T), and coefficient of determination (R2). From the validity test table get the results of the analysis of both variables, namely; workload (x) and work effectiveness (Y) Obtain R-count values > R-Tables. According to the provisions, a variable is said to be valid if the value of R-Calculate > R-Table with a minimum of 0.5. From the reliability test table, the results of all variables have a greater value of Crobach's alpha > 0.6, which means that all variables can meet standard and realistic criteria. From the test table T get the workload sig value (X) 0.019 < 0.5 and the calculated T value 2.495 > 1.69726. This means that there is an effect of workload (X) on work effectiveness (Y). From the R2 test table, the value in the Adjusted R Square is 0.148, which means that the effect of workload (X) on work effectiveness (Y) in the trade service is 54.8%, while the remaining 45.2% is influenced by other variables